Improving Madagascar's Primary Education : A Focus on Schools - Heneveld, Ward (World Bank, Washington, DC, 2012)
This report analyzes the results of research on primary and secondary education in Madagascar in order to identify the school-level factors which have the most influence on student learning and on whether students stay in school. Also included are crude estimates of the resources that will be needed and which might be available to invest in providing or establishing these factors by the year 2000. The study combines analyses of quantifiable issues--economic decline, population growth, the size and internal efficiency of the education system, and education financing--with more qualitative concerns--school climate, the teaching/learning process, and the socio-political and cultural context--in order to capture the multi-faceted reality that will shape the future of primary and secondary education in Madagascar. The focus is on schools. The study examines the factors that determine school effectiveness, and the conditions in schools that help children learn. Central to the study are observational case studies of 12 primary sch, 12 junior secondary (CEG), and 12 senior secondary (lycee) schools that a Technical Group from the Ministry of Education conducted in 1993/94. The results of the primary school cases are compared with a 1991 evaluation of students' achievement and the factors that contribute to that achievement and with a forthcoming study on primary school wastage.